Pocket Book of English for Graphic Technique As Learning Source and Medium of English for Graphic Technique Course - Ika Agustina; Reniwati Lubis; Syahripal Putra (JURNAL ARBITRER, 2019)
The rapid growth of information technology, especially by using devices, linear with practical needs, convenience, and affordability in learning media. Today, the presence of android-based applications is quite widespread, especially in the discipline of educational media and overcoming limitations in the context of learning. Pocket books are a source and medium of learning that, if packaged in a practical and sophisticated way, will be able to provide solutions to learning problems as well as to supply impetus for student interest and learning outcomes. This research aims to develop learning resources and learning media in the sort of a decent and useful Android-based pocket book application as an effort to increase student interest and learning achievement. The research method used is R & D with research subjects, namely students of the Department of Graphic Technique in semester 2. The data collection technique in this research was in the kind of documentation by organizing learning materials based on syllabus through relevant book references and conducting FGD with graphic and ESP experts. Furthermore, to ensure that the pocket book application is feasible, validation was carried out by 6 validators with a value of 4.61 with an excellent category then tested with students' response of 4.57 with a very positive category. Therefore, this application is proven to be able to accommodate the needs of resources and media for learning English for students because it can be a substitute for books that are easy to carry and can be used practically without limitation of time and place.